Novel issues on unsaturated soil mechanics and rock engineering : proceedings of the 2nd GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2018 -- The Official International Congress of the Soil-Structure Interaction Group in Egypt (SSIGE) /: proceedings of the 2nd GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2018 -- The Official International Congress of the Soil-Structure Interaction Group in Egypt (SSIGE). ([2019]) - Unknown
No abstract available